2009
DOI: 10.1162/leon.2009.42.3.231
|View full text |Cite
|
Sign up to set email alerts
|

Materiality, Memory and Imagination: Using Empathy to Research Creativity

Abstract: Based on a paper presented at the sixth Creativity and Cognition conference (13-15 June 2007, Washington, DC), on the theme "Materialities for Creativity," focused on the cultivating and sustaining of creativity.As digital technology becomes increasingly pervasive and embedded into our everyday experience, there is a growing awareness of the significance of physical interaction with the material world [1]. Recent research is providing evidence of the crucial importance of materiality and physical experience i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 7 publications
1
16
0
3
Order By: Relevance
“…In addition, product design using complex structures would require the use of 3D computational design, which may involve tools such as the Grasshopper plug-in for Rhinoceros in visual programming. Unlike the traditional design approach where designers rely on intuition and tacit knowledge to solve problems (Treadaway 2009), computational design enables encoding design decisions using computer language and predefines the steps needed to achieve a result (Kilkelly 2016). Fashion designers and product developers will be expected to adapt to the change in the order of operation in developing various garment structures.…”
Section: Impacts On Design and Product Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, product design using complex structures would require the use of 3D computational design, which may involve tools such as the Grasshopper plug-in for Rhinoceros in visual programming. Unlike the traditional design approach where designers rely on intuition and tacit knowledge to solve problems (Treadaway 2009), computational design enables encoding design decisions using computer language and predefines the steps needed to achieve a result (Kilkelly 2016). Fashion designers and product developers will be expected to adapt to the change in the order of operation in developing various garment structures.…”
Section: Impacts On Design and Product Developmentmentioning
confidence: 99%
“…This ultimately eliminates or reduces post-printing processes such as assembly. Moreover, fashion design and product development have traditionally relied heavily on hand-on based practices and intuitive decision making, and a steep learning curve exists in a digital design adaptation for designers who have more training in haptic skills (Danaher 2004;Harris 2005;Treadaway 2009). For 3DP based wearable product design, scholars (Sun and Parsons 2014) have found that traditional fashion designers would need to efficiently apply their spatial visualization ability (Kozhevnikov et al 2010) and their tacit knowledge in order to effectively translate or convert the conventional handon based tools, procedures, and workflow into the 3D CAD processes.…”
Section: Impacts On Design and Product Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Tangible interfaces that utilize haptic and gestured responses are being developed largely in response to requirements from the computer games industry for more physical interaction with software. Digital technology used to support routine everyday creative practice, however frequently inhibits rather than integrates haptic and sensory capability [25]. Current knowledge concerning touch and its interaction with other sensory modalities: sight, hearing, smell and taste, is limited due to the complexities involved [7].…”
Section: Craft and Experiencementioning
confidence: 99%
“…This paper describes research that is part of a much larger case study concerning the use of digital technology to support the creative process [24] [25]. The investigation cited here focuses specifically on hand craft within hybrid digital practice and provides instances from a case study documenting the creative practice of an artist who uses both digital and physical cut and paste to create her artworks.…”
Section: Introductionmentioning
confidence: 99%